Characterization Porosity on Ceramic Body Stoneware Based Kalimantan Clay - Tussniari, Putu Ekayani Sri; Putra Adnyana, I Gusti Agung; Cingah, Made (BULETIN FISIKA; Vol 19 No 1 (2018): BULETIN FISIKA, 2018)
It has been made ceramic body stoneware using a mixture of Kalimantan clay, RRC feldspar, Belitung kaolin, Belitung quartz and Bukit Jimbaran limestone further coded BPC-1. This study aims to determine the value of dry shrinkage, the effect of sintering temperature of 900 o C and 1200 o C against firing shrinkage, and the influence of sintering temperature of 900 o C and 1200 o C against porosity in the ceramic body stoneware. Ceramic stoneware burned with a temperature variation of 900 o C and 1200 o C. The results show the value of dry shrinkage in ceramic stoneware of 2.9%. Stoneware ceramic firing shrinkage at a temperature of 900 o C combustion of 1.3%, and the combustion at a temperature 1200 o C of 3.8%. Porosity ceramic stoneware at a temperature of 900 o C combustion showed porosity of 10.5%, while the combustion at a temperature 1200 o C of 5.5%. Show that the combustion temperature greatly affects the value of dry shrinkage, firing shrinkage and porosity of stoneware ceramics. The higher the combustion temperature the higher the shrinkage and the decreasing the porosity.